Comprehensive insights into Sitobion avenae preferences and performance on Pakistan’s wheat cultivars leading to identification of potential RNAi targets - Mukhtar, Ruhma; Afzal, Eijab; Noureen, Rabia; Zeeshan, Nadia; Afroz, Amber (Penerbit Universiti Kebangsaan Malaysia, 2024)
Sitobion avenae, a notable hemipteran pest, poses a significant economic threat to Triticum aestivum due to its short generation times and high reproductive rates. Challenges like the development of insecticide resistance, the limited impact of insecticidal genes, and associated risks led to seeking a more precise approach like RNA interference. This study evaluated S. avenae response on seven different local cultivars (Anaj-2021, Subhani-2022, Fakhar-e-Bhakkar-2021, Akbar-2019, Mexi-Pak-2022, Barani-2022, & Dilkash-2022) through aphid preference test, aphid choice assay, and aphid performance test. Further, differential proteomics of S. avenae (pre- and post-feeding on susceptible and resistant wheat cultivars) was performed using Sodium Dodecyl Sulphate-Polyacrylamide Gel Electrophoresis. Among the local wheat cultivars, Anaj-2021 was regarded as the most susceptible cultivar while Barani-2022 was declared the most resistant. The differential proteome analysis of Anaj-2021 (S), and Barani-2022 (R) show 11 upregulated proteins including Glutathione S- transferase, Cathepsin, Carbonic anhydrases, Ecdysone induced protein, Odorant binding protein 3, Heat shock protein, Salivary effector protein, SID1-like protein, Sodium channel protein, chemosensory protein, and trypsin were upregulated in S. avenae on wheat feeding as compared to non-feeding. Trypsin, cathepsin-B and carbonic anhydrases are connected to detoxification and digestion. While odorant binding proteins, salivary effector proteins, sodium channel proteins and ecdysone- induced proteins facilitate feeding process in S. avenae. The enhanced expression of proteins having detoxification, digestion or defense activity implicates their essential role in the survival of S. avenae. Therefore, these proteins have the potential to serve as RNA interference targets, against which double-stranded RNA could be designed and expressed in wheat cultivars to make them resistant to local S. avenae infestation and avert yield loss.